Clinical impact and cost-effectiveness of primary cytology versus human papillomavirus testing for cervical cancer screening in England. Issue 4 (24th May 2019) - Bains, Irenjeet; Choi, Yoon Hong; Soldan, Kate; Jit, Mark
Abstract : Objectives: In England, human papillomavirus (HPV) testing is to replace cytological screening by 2019–2020. We conducted a model-based economic evaluation to project the long-term clinical impact and cost-effectiveness of routine cytology versus HPV testing. Methods: An individual-based model of HPV acquisition, natural history, and cervical cancer screening was used to compare cytological screening and HPV testing with cytology triage for women aged 25–64 years (with either 3- or 5-year screening intervals for women aged under 50 years). The model was fitted to data from England's National Health Service Cervical Screening Programme. Both clinical and economic outcomes were projected to inform cost-effectiveness analyses. Results: HPV testing is likely to decrease annual cytology testing (by 2.76 million), cervical cancer incidence (by 290 cases), and health system costs (by £13 million). It may increase the number of colposcopies, although this could be reduced without leading to more cancers compared with primary cytology by increasing the interval between screens to 5 years. The impact in terms of quality-adjusted life-years (QALYs) depends on the quality of life weight given to colposcopies versus cancer. Conclusions: England's move from cytology to HPV screening may potentially be life-saving and cost-effective. Cost-effectiveness can be improved further by extending the interval between screens or using alternative triage methods such as partial or full genotyping.